THE ROLE OF LITERARY CRITICISM - Farmonov N.D. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. Research on the history of Uzbek literature is still being continued today. It is known that today has put on the agenda the need to change the attitude to our past heritage, the need for a new scientific interpretation of a number of literary events, facts, the fate and activities of creative people. So, the students who are taking lessons today have a huge and difficult and honorable task to study the history of our national literature scientifically and to create a new "History of Uzbek Literature".